(untitled) (Riwayat: Educational Journal of History and Humanities, 2026)
G eneration Z represents a cohort that has grown up in a digital environment characterized by complex psychological dynamics, particularly for those who migrate for educational or employment purposes. Within the Madurese cultural context, resilience is not solely grounded in individual psychological capacities but is deeply embedded in local cultural philosophies Asapok Angin and Abhental Ombhe as well as strong religiosity. This study aims to explore how Madurese Generation Z individuals construct resilience while living abroad through the internalization of cultural values and spirituality. Employing an interpretive paradigm and a phenomenological approach, this research involved two Madurese Generation Z participants residing in Turkey who simultaneously assumed dual roles as students and part-time workers. Data were collected through semi-structured interviews and analyzed using processes of data condensation, categorization, and thematic analysis. The findings reveal that participants’ resilience is shaped through three primary strategies: personal goal commitment, spirituality-based religious support, and social support from fellow Madurese migrants. The philosophies of Asapok Angin and Abhental Ombhe function as moral and motivational frameworks that strengthen individuals’ capacity to endure economic, academic, linguistic, and psychological challenges. These cultural values operate as psychological resources that foster inner calm, hope, and a sense of life meaning amid the pressures of migration. This study highlights the importance of integrating local cultural perspectives into efforts to enhance the psychological resilience of younger generations within a globalized context.